Reflective cracking behaviour for traffic and temperature effects - Minhoto, Manuel J. C. (2008)
This paper presents a study on the influence of the effects of temperature variations, in comparison with traffic effects, on the reflective cracking overlay behavior. It is intended to contribute to the improvement of the pavement overlay design methods which consider reflective cracking as one among distress criteria. The development of this study was based on the numerical simulation of the overlay behavior, through the implementation of numerical thermal and mechanical models based on the finite element, considering the simultaneous action of traffic and temperature variations and their influence on reflective cracking.